Silver Modified Degussa P25 for the Photocatalytic Removal of Nitric Oxide - Neil Bowering; Deborah Croston; Philip G. Harrison; Gavin S. Walker (International Journal of Photoenergy)
A study of the photocatalytic behaviour of silver modified titanium dioxide materials for the decomposition and reduction of nitric oxide (NO) gas has been carried out. The effects of silver loading, calcination temperature, and reaction conditions have been investigated. Prepared photocatalysts were characterised using XRD, TEM, and XPS. A continuous flow reactor was used to determine the photocatalytic activity and selectivity of NO decomposition in the absence of oxygen as well as NO reduction using CO as the reducing agent, over the prepared photocatalysts. XRD and TEM analysis of the photocatalysts showed that crystalline silver nitrate particles were present on the titanium dioxide surface after calcination at temperatures of up to 200∘C. The silver nitrate particles are thermally decomposed to form metallic silver clusters at higher temperatures. XPS analysis of the photocatalysts showed that for each of the temperatures used, both Ag+ and Ag0 were present and that the Ag0/Ag+ ratio increased with increasing calcination temperature. The presence of metallic silver species on the TiO2 surface dramatically increased the selectivity for N2 formation of both decomposition and reduction reactions. When CO was present in the reaction gas, selectivities of over 90% were observed for all the Ag-TiO2 photocatalysts that had been calcined at temperatures above 200∘C. Unfortunately these high selectivities were at the expense of photocatalytic activity, with lower NO conversion rates than those achieved over unmodified TiO2 photocatalysts.